Antimicrobial Properties of Polyester/Copper Nanocomposites by Melt-Spinning and Melt-Blowing Techniques - Alain González-Sánchez; Ricardo Rosas-Macías; José E. Hernández-Bautista; Janett A. Valdez-Garza; Nayeli Rodríguez-Fuentes; Florentino Soriano-Corral; Antonio S. Ledezma-Pérez; Carlos A. Ávila-Orta; Víctor J. Cruz-Delgado (Textiles, 2023)
In this study, textile fiber prototypes based on polyester and different Cu nanoparticles (CuNP) content were produced using melt-spinning to obtain bi-component multifilament fibers and melt-blowing to obtain non-woven fabrics. The prototypes were tested against pathogenic microorganisms such as S. aureus, E. coli, and C. albicans. It was shown that bi-component fibers offer excellent protection against pathogens, with up to 99% growth inhibition with 0.5% w/w for S. aureus and E. coli; meanwhile, non-woven fabric only shows activity against E. coli from 0.1% w/w of CuNP. Using different analytical techniques, it was possible to identify that the CuNP were confined exclusively in the outer cover of the bi-component fibers which may be associated with increased antimicrobial activity compared to the fibers in the non-woven fabric. The use of polymeric nanocomposites based on polyester/copper offers an alternative of great interest due to the versatility of the raw material and the high efficiency of copper nanoparticles as an antimicrobial additive.